Sejarah Peradaban Islam Dalam Perspektif Ibnu Katsir - Rahma, Farida Nur; Kusumah, Mada Wijaya; Hidayat, Tatang; Supraha, Wido (PT. Student Rihlah Indonesia, 2025)
The purpose of this study is to analyze the history of Islamic civilization in the perspective of Ibn Kathir. Using the literature study method, the researcher found that Ibn Kathir is a superior scholar who earned the title of Al-Hāfidzh, Al-Muhaddits, Al-Fāqih, Al-Mu'arrikh and Al-Mufassir with amazing works. Through his historical works, Ibn Kathir indirectly established a methodology for reconstructing historical events starting from collecting sources of history, criticizing sources with hadith science, interpretation and writing represented by nuqil. As for when Ibn Kathir compiled the book Al-Bidāyah wa an-Nihāyah, he compiled it with a distinctive periodization so as to avoid us from the view that the time of the Prophet ﷺ was a classic or ancient period. The glory of Islamic civilization that was built from the time of the Prophet ﷺ can be repeated by retracing the steps as exemplified by the Prophet and the Sahabat. Because the steps of the Prophet ﷺ in building civilization are steps guided by revelation, this book of revelation is a valuable legacy for the reconstruction of Islamic civilization in the future. The civilization that materializes is not a patchwork civilization but a distinctive civilization that is able to create an Islamic society.